Harmonisasi Kehutanan dan Sinergi Hukum Adat: Evaluasi Kebijakan Pemulihan dan Pemberdayaan Masyarakat pada Restorasi Eks Lahan Sawit Ilegal di Aceh - Misbah, T. Lembong (Yayasan Kawanad, 2024)
This research explores the synergy of customary law principles, forestry harmonization, and community empowerment in the restoration of illegally converted palm oil land in Aceh Tamiang. The research method involves document analysis, stakeholder interviews, and field surveys. The results indicate that the synergy of customary law principles and the implementation of forestry law principles have a positive impact on the recovery of illegally converted palm oil land. Forestry harmonization enables active community participation, with empowerment as a key factor in natural resource management, bridging the understanding of customary and forestry law. The evaluation of the Aceh Government's restoration policy in Aceh Tamiang highlights positive impacts on ecology and environmental balance. This program, through cross-sector collaboration, not only enhances positive community behavior but also supports the concepts of development and empowerment. The research conclusion provides insights for policymakers, legal practitioners, and relevant parties to develop a holistic approach to land conflict resolution, involving communities in restoration efforts, and strengthening local capacity to manage natural resources. These findings serve as a foundation for policy improvement and the implementation of similar programs to support environmental sustainability and community well-being in Aceh Tamiang.